Slope failure analysis using chromaticity variables - Othman, Rashidi; Hasni, Shah Irani (Intech, 2017)
Slope failure has become a major concern in Malaysia due to the rapid development and urbanisation in the country. It poses severe threats to any highway construction industry, residential areas, natural resources, as well as tourism activities. Thus, this study aims to characterise the relationship between chromaticity variables to be manipulated as indicators to forecast slope failure. The concentration of each soil property in slope soil was evaluated from two different localities that consist of 120 soil samples from stable and unstable slopes located along North South Highway and East West Highway. Indicators that could be used to predict shallow slope failure were high value of variable L*(62), low values of variables c* (20) and h* (66). Furthermore, the hues that indicate stable slope based on Munsell Soil Colour Chart are between 2.5YR and 5YR while the hues that indicate unstable slope are between 5YR and 10YR. The overall analysis leads to the conclusion that the reactions and distinctive changes of chromaticity variables between stable and unstable slopes were emphasised as results of significant differences between soil properties, the locations, slope stability and combinations of all interactions.